Nepal : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2003)
This Statistical Appendix paper for the periods between 1996/97 and 2001/02 for Nepal discusses both nominal and real gross domestic product by sector; savings and investments; agricultural production and yields; Manufacturing Production Indices; energy consumption; tourism indicators; Consumer Price Index; summary of government operations; central government expenditure by economic classification; profits and losses of selected nonfinancial public enterprises; assets and liabilities of commercial banks and companies; balance of payments; composition of foreign trade and exports; summary of tax system; and other statistical data.